Certain soil characteristics and light conditions of enzyme activities and variance conditional to plant type - Kravkaz Kuscu, Inci Sevinc (Springer Science and Business Media LLC, 2020)
Soil is one of the most important factors in plant cultivation, and its content affects plant growth significantly. However, soil composition and characteristics vary depending on the environmental conditions in the area where the soil is located. In this study, urease and catalase enzyme activities in plant soils grown under different shade conditions were examined. The Prunus cerasifera, Tilia tomentosa, Gleditsia triacanthos, Euonymus japonica, and Betula pendula species were grown in five different light conditions during one vegetation period, and the urease and catalase enzyme activities and Ph, EC (mS.cm ̄1), CaCO3 (%), OM (%), P (ppm), and K (ppm) changes were examined within the scope of the study. As a result, it was found that characteristics other than Ph, which was the subject of the study, changed to a great extent depending on the plant species and light conditions; however, in the areas where different plant species were grown, the soil characters changed at different levels depending on the light. As a result of the study, the highest values in many characteristics were obtained under 45% and 65% light conditions.
Keywords: Soil; Plant Development; Soil Pollutants; Betula; Soil Microbiology; Environmental Monitoring; Enzymes; 2. Zero hunger; 15. Life on land